The Role of Emotional Intelligence toward Internalizing and Externalizing Problems in Adolescents - Febriannor, Muhammad; Syakarofath, Nandy Agustin; Widyasari, Dian Caesaria; Karmiyati, Diah (Gadjah Mada Journal of Psychology (GamaJoP), 2024)
People experience more rapid physical, social, and emotional development in adolescence than in any other developmental stage. The dramatic changes may cause them volatile mental conditions and difficulties in overcoming various behavioral problems summarised as internalizing (IP) and externalizing problems (EP). One of the protective factors is emotional intelligence (EI) because someone with good emotional intelligence can control emotions when angry and adapt to unpleasant situations. This study aimed to determine the role of EI on IP and EP in Indonesian adolescents. This study used a quantitative research design with a simple random sampling technique. The research subjects were adolescents aged 15 to 18 years (N = 300) who attended nine high schools in East Java, consisting of 96 males and 204 females. The research instruments used were the Schutte Emotional Intelligence Scale (SEIS) and the Strength and Difficulties Questionnaire (SDQ). The results showed a significant negative role between emotional intelligence and internalizing problems (R2 =.391; F(1,298) = 191.649; p <.001) and externalizing problems (R2 =.281; F(1.298) = 116.230; p <.001). The higher one's ability to understand, regulate, and use emotions, the lower the manifestation of internal and external problematic behavior. It means that EI is confirmed to predict the IP and EP. The way to advance the capacity of adolescents' emotional intelligence is to try to express emotions and regulate and utilize their feelings. So adolescents do not develop mental health problems.